Pengaruh Beban Kerja Dan Motivasi Kerja Terhadap Kinerja Karyawan Pada PT ABC - Hanna Luthfiana; Rycha Kuwara Sari; Ferawaty Puspitorini (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2024)
This research aims to determine whether there is a significant influence between workload and work motivation on employee performance at PT ABC. The method used in this research is a quantitative method. The sampling technique used in this research is saturated sampling or the entire population is sampled. The population in this study was 55 respondents. Data analysis using Smart-PLS 4 software and hypothesis testing, namely the t test (partial test). The results of this study show that (1) the workload has a significant effect on employee performance at the PT ABC and (2) the work motivation has a significant effect on employee performance at the PT ABC.